Microstructural analysis of sintered pure-titanium and titanium/hydroxyapatite (HA) surgical implant materials under different temperatures and HA doped conditions produced by powder metallurgy - AYGÜL, EBUZER; YALÇINKAYA, SENAİ (IOP PUBLISHING LTD, 2020)
In this study, pure titanium and hydroxyapatite (HA) doped titanium alloys used as Surgical Implant Materials by weight percentage (wt%) of 5% and 10% were sintered by powder metallurgy method. Total 9 samples of these alloys are produced, three of them are pure titanium's, which are sintered at 900, 1000 and 1150 degrees C temperatures, respectively, for 4 h. From the rest of 6 samples, 3 samples were added 5 wt% HA and the last 3 samples were produced by doped 10 wt% HA. Titanium alloys produced by admixture with HA are sintered for 4 h at 900, 1000, 1150 degrees C temperatures, respectively. Titanium and HA powders were milled for 2 h in a ball-milling mixer and then pressed for half an hour at 20 MPa pressure. EDX, SEM, XRD and Vickers hardness tests were carried out for the analysis of the samples. As a result of the analysis, it was observed that different sintering temperatures caused to various Vickers hardness values and micro-structural changes occurred for pure titanium and HA doped titanium alloys. In addition, multiple phase and Ti plus HA structures were detected in XRD diffractometers of the samples at these temperatures. Most importantly, for the first time in our study, P3Ti5 phase was revealed with 00-045-0888 > XRD card. Finally, the effects of sintering temperatures and HA-doped amounts on particle sizes and pore sizes of the samples were determined by SEM analysis.
Keywords: titanium; hidroxyapatite; powder metallurgy; microstructure; tempeture; hardness; SEM; XRD